Nlcam modulates midline convergence during anterior neural plate morphogenesis - Browne, Katherine E.; Wittbrodt, Joachim (Developmental biology, 2010)
During development, different cell types must undergo distinct morphogenetic programs so that tissues develop the right dimensions in the appropriate place. In early eye morphogenesis, retinal progenitor cells (RPCs) move first towards the midline, before turning around to migrate out into the evaginating optic vesicles. Neighbouring forebrain cells, however, converge rapidly and then remain at the midline. These differential behaviours are regulated by the transcription factor Rx3. Here, we identify a downstream target of Rx3, the Ig-domain protein Nlcam, and characterise its role in regulating cell migration during the initial phase of optic vesicle morphogenesis. Through sophisticated live imaging and comprehensive cell tracking experiments in zebrafish, we show that ectopic expression of Nlcam in RPCs, as is observed in Rx3 mutants, causes enhanced convergence of these cells. Expression levels of Nlcam therefore regulate the migratory properties of RPCs. Our results provide evidence that the two phases of optic vesicle morphogenesis: slowed convergence and outward-directed migration, are under different genetic control. We propose that Nlcam forms part of the guidance machinery directing rapid midline migration of forebrain precursors, where it is normally expressed, and that its ectopic expression upon loss of Rx3 imparts these migratory characteristics upon RPCs.